An eco-hydrological approach to predicting regional vegetation and groundwater response to ecological water conveyance in dryland riparian ecosystems. (4th September 2015) - Han, Ming; Zhao, Chengyi; Feng, Gary; Disse, Markus; Shi, Fengzhi; Li, Juyan
Abstract: The ecosystem along the lower reach of Tarim River has been undergoing remarkable changes due to the ecological water conveyance activity since 2000. To improve the scientific basis of riparian restoration, the clearing understanding of the dynamic of eco-hydrological system and the feedback between hydrological and ecological components are needed. A fully distributed eco-hydrological model combines a hydrology component based on the modified MODFLOW, with a vegetation dynamic component described by Verhulst logistic equation. The validation of the eco-hydrological model using groundwater well observation, river stage observation and remote sensing data demonstrated that the good capability of the model in simulating the dynamic of the eco-hydrological system in lower reach of Tarim River. The interaction between the hydrological component and ecological component has been revealed through water balance analysis and scenario studies. Vegetation has a significant impact on groundwater evapotranspiration, groundwater storage change and groundwater depth, while groundwater depth is a critical feedback variable that determines the vegetation dynamics, which is shown by observation and simulation result. The eco-hydrological model represented in this study could help to groundwater dependent ecosystem restoration and protection, particularly for riparian ecosystem.